The Impact of Human Resource Management and Member Motivation on Member Engagement in the Jakmania Cirebon - Muhammad Rizky; Dharliana Hardjowikarto; Juwita Juwita (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the influence of human resource management and member motivation on member involvement in The Jakmania Cirebon community. The study used an associative quantitative approach with 70 active members of respondents selected through purposive sampling techniques. Data collection was carried out using a questionnaire based on the Likert scale, while data analysis used the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS. The results of the study show that human resource management does not have a significant effect on member engagement, so organizational structural mechanisms have not been the main factor in encouraging the participation of supporter community members. Conversely, member motivation has a positive and significant effect on member engagement.